ANALYSIS OF HIGH SCHOOL STUDENTS CRITICAL THINKING ABILITY TO SOLVE SOCIAL SCIENCE PROBLEMS: Received: 21st May 2021; Revised: 15th September 2021, 11th November 2021, 1st January 2022; Accepted: 5th January 2022 - Suroso, Joko; Indrawati, .; Sutarto, .; Mudakir, Imam (MATTER: International Journal of Science and Technology, 2022)
Teaching physics as one domain subject in school sometimes got less attention on how to measure the critical thinking ability which is a fundamental case to elevate and reach high order thinking. This study was aimed to analyze the critical thinking ability of high school students in the Jember district to break down the social science cases. The method used to analyze the data was descriptive qualitative which took in writing test technique. Based on the data analysis, the result showed that the critical thinking ability was able to solve social science cases only in the medium category. Thus, it could be concluded that students who were less in critical thinking ability were needed to be elevated to break down the case about social science problems through a proper teaching and learning process.